The role of novel risk markers in cardiovascular disease - Leong, Tora (Trinity College (Dublin, Ireland). School of Medicine. Discipline of Clinical Medicine, 2011)
Cardiovascular disease (CVD) is the leading cause of death in Ireland and globally. Conventional risk factors such as blood pressure, cholesterol and smoking account for most of CVD. A small but significant residual risk is accounted for by novel risk markers. Asymmetric dimethylarginine (ADMA), CD40 ligand and the metabolic syndrome are novel risk markers that are of particular interest because they are strongly associated with endothelial dysftinction and inflammation, both key pivotal processes in atherosclerosis.
Keywords: Clinical Medicine, Ph.D.; Ph.D. Trinity College Dublin